THE IMPACT OF TRANSLATION TECHNIQUES TOWARD THE QUALITY OF TRANSLATION: A Case Study on a Social Text - Havid Ardi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2016)
Quality of translation is one of the most important aspect in translation studies. This article aims at reporting the impact of translation techniques toward the quality of translation in term of accuracy, acceptability, and readibility. This descriptive qualitative research focused on single case. Objective data were taken from the “Asal-usul Elite Minangkabau Modern: Respons terhadap Kolonial Belanda Abad XIX/XX” and its source text “The Minangkabau Respons to Dutch Colonial Rule in the Nineteenth Century”. Then, affective data were taken from the informants. The four of the most frequent techniques which influence the quality of the translation are amplification, literal translation, establish equivalence and modulation. Moreover, the translation quality is categorized good as the score of accuracy is 3.33, acceptability 3.53, and readibility 3.55 in the range of 1-4.